Preparation method of pi-pi conjugated molecule confinement polymerization graphene composite film material
By using continuous external force stretching and π-π conjugated molecules in the preparation of graphene films, the problems of graphene nanosheet orientation and density are solved, and high-strength and high-modulus graphene composite films are achieved. , significantly improves tensile strength and Young's modulus.
Patent Information
- Application Number
- CN202411416661.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-11
AI Technical Summary
The prior art is difficult to achieve highly ordered orientation, strong interfacial action and densification of graphene nanosheets during assembly, resulting in the tensile strength of the graphene composite film being much lower than the tensile strength of the intrinsic graphene monolith.
By preparing graphene oxide gel films and using continuous external tension to inhibit capillary contraction during the film preparation process, the high orientation of nanosheets is induced, combining the interface synergistic effect of covalent bonds and π-π interactions, 10,12- The 25-carbon diyne-1 alcohol and the π-π conjugated long-chain molecules with phenanthroline rings at both ends are polymerized in a domain-limited manner to form a graphene composite film with high strength and high modulus.
The highly oriented and dense structure of the graphene composite film was achieved, and the tensile strength was increased to 708.68-1968.01 MPa, and the Young's modulus was 24.30-107.67 GPa, which significantly improved the mechanical properties of the film.
Smart Images

Figure CN119240677A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a π-π conjugated molecule confined polymerization graphene composite film material, and belongs to the field of nano composite material preparation. Background Art
[0002] There are many methods reported to assemble graphene nanosheets into macroscopic films, such as solution evaporation (ACSNano 2014, 8, 9511.), doctor blade coating (Science 2024, 385, 62.), centrifugal casting (Adv. Mater.2020, 32, 1907411.), super-spreading orientation (Nature 2020, 580, 210.), layer-by-layer self-assembly (Science2015, 348, 2491.), ordered assembly (Nat. Commun. 2018, 9, 1.), interface cross-linking (Science 2021,374, 96.), pore filling (Nat. Commun. 2020, 11, 2077.), and confined assembly (Science 2024, Strategies such as the 3D nanomaterials (Science 2013, 383, 771) have been used to improve the mechanical properties of two-dimensional nanomaterials and have achieved remarkable results. However, the two-dimensional nanomaterials assembled by wet chemical methods will inevitably undergo capillary shrinkage during the drying process as the solvent evaporates, causing more wrinkles on the nanosheets, which seriously affects the mechanical properties of the materials. The researchers reduced the capillary shrinkage to a certain extent by increasing the contact angle between the nanosheets and the liquid and replacing the solvent, and prepared self-supporting materials, but they still could not simultaneously achieve high orientation and dense stacking of two-dimensional nanosheets (Science 2013, 341, 534).
[0003] Since carbon in graphene nanosheets is sp 2 Hybridization, the researchers prepared a double-headed pyrene ring molecule bispyrenyl butyrate (PSE-AP) to form a π-π conjugation with graphene nanosheets and Cr 3+ The strength of the graphene composite film prepared by ionic crosslinking and interface synergy is as high as 821 MPa (Adv. Mater. 2018, 30, 1802733.). The strength of the graphene composite film prepared by the covalent bond and π-π conjugated interface synergy between PCO and PSE-AP is as high as 945 MPa (PNAS2018, 115, 5359.). By preparing a double-headed π-π conjugated long chain molecule (BPDD) containing a vicinal alkyne structure, the strength can reach 1054 MPa under π-π conjugation (Matter 2019, 1, 389.).
[0004] In recent years, external force traction strategies have been widely used to eliminate wrinkles and defects in graphene nanomaterials (Nat. Mater. 2021, 20, 624.). Intercalation plastic stretching of graphene oxide films prepared by blade coating has been proven to effectively eliminate wrinkles in GO nanosheets (Nat. Commun. 2020, 11, 1.), while the reduction strategy is used to fix the ordered orientation structure of the nanosheets and achieve close stacking of the nanosheets (Nat. Mater. 2021, 20, 624.).
[0005] Nevertheless, the tensile strength of the graphene composite films obtained so far is much lower than that of the intrinsic graphene single sheet. Therefore, it is still a big challenge to obtain high-performance macroscopic graphene composite films by assembling graphene oxide nanosheets. The regular orientation, interface interaction and packing density of nanosheets are the key factors affecting the mechanical properties of two-dimensional nanomaterials. How to achieve highly ordered orientation, strong interface interaction and densification of graphene nanosheets during the assembly process is still a huge challenge.
[0006] Related studies have shown that water between graphene gel layers can maintain the orderly stacking of graphene nanosheets and prevent the agglomeration of graphene nanosheets. This is mainly because the surface of graphene nanosheets contains negatively charged hydrophilic functional groups. In the presence of interlayer water, electrostatic repulsion and hydration can separate graphene nanosheets from each other, thereby maintaining an orderly stacking state (Adv. Mater. 2011, 23, 2833.). Based on this, by reducing the capillary shrinkage of the film during the drying process, the high orientation of the nanosheets can be maintained, ensuring that the film has a high degree of orientation.
[0007] At present, the relevant patents on the improvement of graphene composite film mechanical materials by π-π conjugation are as follows:
[0008] A method for preparing a high-strength, high-conductivity, fatigue-resistant and corrosion-resistant graphene composite film (CN108622884A), a method for preparing a super-strong and high-conductivity graphene composite film with π-π conjugation and covalent bond orderly cross-linking (CN108516538A), a method for preparing a long-chain conjugated π bond cross-linked super-tough and high-conductivity graphene composite film (CN109956465A), a method for preparing an in-plane isotropic highly oriented and densely packed graphene film (CN111807355A), a method for preparing a graphene titanium carbide cross-linked film material and its application in supercapacitors (CN202211519772).
[0009] However, these patents only prepare graphene composite films through simple double-headed π-π conjugated molecular interface action with pyrene rings, and the improvement of mechanical properties is limited. There are no patents on improving the mechanical properties of graphene composite films by using double-headed π-π conjugated long-chain molecules with phenanthroline rings and alkyne structures. Summary of the invention
[0010] The problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a method for preparing a graphene film material, which can successfully prepare a graphene film with high orientation, high strength and high modulus.
[0011] The present invention provides a method for enhancing graphene composite film materials by confined polymerization of π-π conjugated molecules. First, a graphene oxide gel film is prepared. During the film preparation process, continuous external force stretching is used to suppress capillary contraction, induce high orientation of nanosheets, and achieve efficient stress transfer through the interface synergistic effect of covalent bonds and π-π interactions to prepare highly oriented and dense graphene composite films. The graphene composite film (US-SB-rGO) material exhibits a tensile strength of 708.68-1968.01 MPa and a Young's modulus of 24.30-107.67 GPa. The improvement in tensile strength is mainly due to the formation of ester covalent bonds between the carboxyl groups at the edge of graphene oxide (GO) and the hydroxyl groups of 10,12-pentadiynol (PCO) under continuous stretching, as well as the synergistic effect between the graphene nanosheets and the π-π conjugated long-chain molecules (BPATD) with phenanthroline rings at both ends, and the confined polymerization of PCO and BPATD under ultraviolet light, which effectively inhibits the capillary shrinkage of the film during the preparation process, ensuring a highly oriented and dense structure of the film. In addition, wide-angle X-ray scattering proves that inhibiting capillary shrinkage can effectively improve the orientation of the film. Porosity calculation and scanning electron microscopy structure characterization of the film cross-section also confirm that inhibiting capillary shrinkage can effectively improve the density of the film.
[0012] In the present invention, the orientation degree is represented by the Herman orientation factor.
[0013] The present invention is achieved through the following technical solutions:
[0014] First, high-quality single-layer large graphene oxide nanosheets (sheet diameter 5-60 mm) were obtained by low-temperature centrifugal exfoliation using a modified Hummers method. μm) aqueous dispersion; secondly, the nanosheets are assembled into GO gel film by vacuum filtration, film casting, doctor blade coating or centrifugal casting; thirdly, the nanosheets are induced to be highly oriented by continuous external force stretching, and the capillary shrinkage of the film during the drying process is suppressed. The ester covalent bond is formed between the carboxyl group at the edge of graphene oxide and the hydroxyl group of 10,12-pentadiyne-1-ol (PCO). Then, the covalently bonded graphene oxide composite film (US-CGO) is reduced to obtain a covalently modified graphene film material. Then, the graphene nanosheets and the π-π conjugated long chain molecules (BPATD) containing phenanthroline rings at both ends form a π-π interface synergistic effect, and PCO and BPATD are confined under ultraviolet light, which further effectively suppresses the capillary shrinkage of the film and ensures the highly oriented and dense structure of the film (US-Cπ-rGO). Finally, the ordered cross-linked film is irradiated with 254 nm and 365 nm ultraviolet light for 2 h, and its Herman orientation factor is 0.871-0.970, preferably the Herman orientation factor is 0.901-0.970; the porosity of the graphene cross-linked film (US-SB-rGO) material is 3.20-25.68%, preferably the porosity is 3.2-10%.
[0015] A method for preparing a graphene film material of the present invention comprises the following steps:
[0016] (1) reacting a raw material of 325 mesh graphite powder with 98 wt% concentrated sulfuric acid (H2SO4) and potassium permanganate (KMnO4) at low temperature, washing, centrifugal exfoliation to prepare a single-layer graphene oxide (GO) nanosheet (sheet diameter 5-60 μm) aqueous dispersion; preferably, the low temperature is 5°C to 10°C;
[0017] (2) subjecting the aqueous dispersion of the single-layer graphene oxide GO nanosheets (sheet diameter of 5-30 μm) described in step (1) to closed oscillation for 5-15 min, and then to centrifugal separation to obtain a graphene oxide GO gel with a concentration of 8-10 mg / ml,
[0018] (3) The graphene oxide (GO) gel obtained in step (2) is formed into a hydrogel film with a thickness of 100-1200 μm on a hydrophilic polyvinylidene fluoride (PVDF) porous substrate; preferably, the film forming process includes suction filtration, cast film, doctor blade coating or centrifugal casting.
[0019] (4) In the step (4), the graphene oxide gel film is plasticized and stretched under the action of an external tensile force, and then maintained in a stretched state.
[0020] (5) covalently cross-linking the graphene oxide (US-GO) film obtained in step (4) with long-chain hydroxyl-containing molecules under continuous external tensile force to obtain a covalently cross-linked graphene oxide film (US-CGO); preferably, the cross-linking agent is a dichloromethane (DCM) solution of 10,12-pentacadiyn-1-ol (PCO);
[0021] Preferably, the crosslinking agent is 10,12-pentacosadiyn-1-ol (PCO) dispersion at a concentration of 15 mM;
[0022] Preferably, the soaking reaction time is 1-3 h, and the PCO mass fraction is 0.5-3%;
[0023] (6) In the step (5), under continuous stretching, HI reduction is used to obtain a covalently cross-linked graphene film (US-CrGO), and continuous external force stretching during the reduction and cleaning process suppresses the capillary shrinkage of the solvent; wherein the preferred reduction time is 12 h;
[0024] (7) The covalently cross-linked graphene film (US-CrGO) in step (6) is immersed in a BPATD dispersion to obtain an ordered cross-linked graphene film (US-CπrGO). Preferably, the concentration of BPATD is 10 mM; preferably, the immersion reaction time is 12-48 h, and the mass fraction of BPATD is 5-15%.
[0025] (8) The ordered cross-linked graphene film (US-Cπ-rGO) obtained in step (7) is subjected to external tensile force, washed, and confined polymerization under 254 nm and 365 nm ultraviolet light, respectively, to prepare an ordered cross-linked graphene film (US-SB-rGO); preferably, the detergent is N,N-dimethylformamide (DMF), the ultraviolet light wavelength is 254 nm, the light efficiency is 30 W, and the illumination time is 2 h; preferably, the ultraviolet light wavelength is 365 nm, the light efficiency is 500 W, and the illumination time is 2 h;
[0026] (9) In the step (8), the π-π conjugated molecule confined polymerization enhanced graphene composite film (US-SB-rGO) prepared by continuous stretching by external force has a Herman orientation factor of 0.718-0.970, preferably a Herman orientation factor of 0.901-0.970; the porosity of the graphene cross-linked film (US-SB-rGO) material is 3.20-25.68%, preferably a porosity of 3.2-10%, and the thickness of the graphene cross-linked film material is 0.5-10 μm, characterized in that: the tensile strength of the ordered cross-linked graphene composite film (US-SB-rGO) is 1.97 GPa, and the modulus is 107.67 GPa.
[0027] Principle of the present invention: The present invention first uses high-quality single-layer graphene oxide (GO) nanosheets (sheet diameter of 5-60 μm) as raw materials, concentrates and scrapes to prepare GO gel film, and then effectively suppresses the capillary contraction of the film by continuous stretching to prepare a highly oriented graphene oxide film. Then, under the action of continuous external force stretching, the graphene oxide film reacts with PCO to generate ester covalent bonds, which effectively ensures the highly oriented structure of the film. The prepared graphene oxide film (US-CGO) is then subjected to reduction and π-π conjugated cross-linking treatment of BPATD. Finally, the small molecule PCO and the alkyne structure in BPATD are confined and polymerized under ultraviolet light, and carbon-carbon double bond covalent bonds are introduced to prepare a high-strength graphene composite film (US-SB-rGO).
[0028] At the same time, compared with the existing method for preparing graphene composite film materials, the advantages of the present invention are:
[0029] (1) The graphene gel film is stretched by continuous external force to effectively suppress the capillary shrinkage during the film drying process, so that the film has a highly oriented structure;
[0030] (2) The covalent bonds and π-π conjugated interactions between PCO and BPATD and graphene nanosheets, and the confined polymerization of the alkyne structures in PCO and BPATD under ultraviolet light, effectively inhibit the capillary shrinkage of graphene during the drying process, further enhance the highly oriented structure, and effectively reduce the porosity of the film;
[0031] (3) The interfacial synergistic effect of covalent bonds and π-π interactions enables the stress to be effectively transferred between nanosheets, resulting in the excellent mechanical properties of the graphene composite film (US-SB-rGO), including a tensile strength of 1.97 GPa and a modulus of 107.67 GPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The present invention is a process flow chart of a π-π conjugated molecule confined polymerization graphene composite film material.
[0033] Figure 2The present invention is a schematic diagram of the preparation process of a π-π conjugated molecule confined polymerization graphene composite film material. First, the graphene oxide gel film is continuously stretched by external force to suppress the capillary contraction of water molecules and prepare a highly oriented graphene oxide film. Then, PCO covalently modifies the graphene oxide film to prepare a US-CGO film, and the US-CGO film is reduced with hydroiodic acid (HI) to obtain a highly oriented US-CrGO. Subsequently, BPATD is used to perform π-π conjugated cross-linking on the US-CrGO to prepare a graphene composite film US-Cπ-rGO. Finally, the small molecule PCO and the alkyne in BPATD undergo confined polymerization under ultraviolet light irradiation, thereby preparing a highly oriented, dense, and high mechanical properties graphene composite film US-SB-rGO.
[0034] Figure 3 Evidence for the improvement of film orientation and density in the preparation method of a π-π conjugated molecule confined polymerized graphene composite film material in the present invention: A, focused ion beam cutting cross-section scanning electron microscope (FIB-SEM) photograph of the confined ordered cross-linked graphene composite film (US-SB-rGO); B, focused ion beam cutting cross-section scanning electron microscope (FIB-SEM) photograph of the reduced graphene oxide film (rGO); C, porosity comparison chart of reduced graphene oxide (rGO) film and confined ordered cross-linked graphene composite film (US-SB-rGO); D, wide-angle X-ray scattering spectra of reduced graphene oxide film (rGO) and confined ordered cross-linked graphene composite film (US-SB-rGO).
[0035] Figure 4 Evidence for the confined polymerization of polymer in the film in the preparation method of a π-π conjugated molecule confined polymerization graphene composite film material in the present invention: A, the scattering vector q diagram of the film material is characterized by wide-angle X-ray scattering; B, the interlayer spacing of the film material is characterized by an X-ray scatterer; C, differential scanning calorimetry characterization of polymer BPATD, SB-rGO film of Example 6 and US-SB-rGO film of Example 2; D, cross-sectional TEM photo of the rGO film of Example 9; E, cross-sectional TEM photo of the SB-rGO film of Example 6, F, cross-sectional TEM photo of the US-SB-rGO film of Example 2.
[0036] Figure 5The film mechanical properties of the preparation method of a π-π conjugated molecule confined polymerization graphene composite film material in the present invention (Example 3). A, stress-strain curve of reduced graphene oxide film (rGO) and confined ordered assembled graphene composite film (US-SB-rGO); B, scanning electron microscope (SEM) photo of the cross section of confined ordered assembled graphene composite film (US-SB-rGO); C, in-situ tensile Raman G peak shift spectrum of confined ordered cross-linked graphene composite film (US-SB-rGO); D, stress relaxation curve of reduced graphene oxide (rGO) film and confined ordered cross-linked graphene composite film (US-SB-rGO); E, scanning electron microscope (SEM) photo of the cross section of reduced graphene oxide (rGO) film; F, in-situ Raman spectrum of reduced graphene oxide (rGO) film; G, tensile strength-Young's modulus comparison diagram of confined ordered cross-linked graphene composite film (US-SB-rGO) and graphene films prepared by different preparation methods reported in the literature. DETAILED DESCRIPTION
[0037] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. However, the following embodiments are limited to explaining the present invention, and the protection scope of the present invention should include the entire contents of the claims, and through the description of the following embodiments, those skilled in the art can fully implement the entire contents of the claims of the present invention.
[0038] The method of the present invention is implemented as follows: Figure 1 and Figure 2 As shown, Figure 1 This is a process flow chart of a π-π conjugated molecule confined polymerization graphene composite film material in the present invention. Figure 2 The present invention is a schematic diagram of the preparation process of a π-π conjugated molecule confined polymerization graphene composite film material. First, the graphene oxide gel film is continuously stretched by external force to suppress the capillary contraction of water molecules and prepare a highly oriented graphene oxide film. Then, PCO covalently modifies the graphene oxide film to prepare a US-CGO film, and the US-CGO film is reduced with hydroiodic acid (HI) to obtain a highly oriented US-CrGO. Subsequently, BPATD is used to perform π-π conjugated cross-linking on the US-CrGO to prepare a graphene composite film US-Cπ-rGO. Finally, the small molecule PCO and the alkyne in BPATD undergo confined polymerization under ultraviolet light irradiation, thereby preparing a highly oriented, dense, and high mechanical properties graphene composite film US-SB-rGO.
[0039] The graphene oxide described in the present invention is a two-dimensional nanosheet containing rich oxygen-containing functional groups, which can form an ester covalent bond with a small molecule PCO; the π-π conjugated long-chain molecule (BPATD) has phenanthroline rings at both ends and can form a π-π interaction with the graphene nanosheet; PCO and BPATD alkyne structures are confined and polymerized under ultraviolet light to prepare a confined ordered cross-linked composite film (US-SB-rGO), and the film has a thickness of 0.5-10 μm.
[0040] In the following embodiments of the present invention, the following testing method is adopted:
[0041] A: The tensile strength test method comprises the following steps: cutting the prepared ordered cross-linked graphene composite film into a test strip with a length of 12 mm and a width of 3 mm, and fixing the strip on a paper test template with a span of 0.5 cm, and using a Shimadzu AGS-X tensile tester equipped with a 100 N sensor to test the tensile performance of the test strip at a tensile speed of 0.5 mm / min to obtain the stress-strain curve of the film. Wherein the tensile strength = the tensile force when the test strip breaks / the cross-sectional area of the test strip.
[0042] B: The porosity test method includes the following steps: film porosity = 1-film measured density / film theoretical density, wherein film measured density = film mass / film volume, and film theoretical density is calculated based on the content of each component of the composite film.
[0043] C: Young's modulus test method: Young's modulus is obtained by calculating the slope of the elastic region of the stress-strain curve.
[0044] Example 1
[0045] Add 24 mL of concentrated sulfuric acid (98 wt%) to a 1000 mL beaker and cool to 5 °C in an ice bath. Slowly add 1.0 g of graphite powder (325 mesh) (Qingdao Jinrilai Co., Ltd.) and stir magnetically at 5 °C for 1.5 h at a stirring speed of 500 rpm. Slowly add 3.0 g of KMnO4 within 2.0 h, always controlling the temperature at 5 °C, and continue stirring for 10 h after addition. Use a syringe pump to add 50 mL of pre-frozen deionized water, always controlling the temperature at 5 °C for about 8.0 h, and continue stirring for 1 h after addition. Pour the reaction mixture into 700 mL of pre-frozen deionized water to terminate the reaction. Slowly add 20 mL of H2O2 (30 %) and stir for 20 min. Place the mixture in a refrigerator to settle overnight (2-4 °C). Centrifuge 3 times with dilute HCl (3.7 wt%) at 2-4 °C at 10,000 rpm for 5 min to remove Mn. 2+. Centrifuge 4 times at 10,000 rpm for 5 min with deionized water at 2-4 °C to remove excess acid. Centrifuge 3 times at 3,000 rpm for 10 min to remove the supernatant to separate the unpeeled particles. Centrifuge the obtained supernatant at 10,000 rpm for 10 min to obtain the precipitate, and disperse the obtained precipitate in deionized water at 2-4 °C to make 2 mg mL -1 The dispersion was stored in a refrigerator (2-5 °C) to obtain a large single-layer GO dispersion with a sheet size of 5-60 μm.
[0046] Example 2
[0047] Take 30 mL of the GO dispersion (2 mg mL -1 ) was placed in a 50 mL centrifuge tube and centrifuged at 10000 rpm for 10 min to obtain GO gel. After fully removing the bubbles in the gel, the graphene oxide gel film was prepared by scraping on a hydrophilic polyvinylidene fluoride (PVDF) porous substrate. The gel film was then transferred to a stretching device and dried naturally by continuous stretching to obtain a US-GO film. The film was kept in a stretched state and soaked in a 15 mM PCO DCM solution for 2 h, then washed with DCM 3 times, and then reduced with 38 wt% hydroiodic acid for 12 h. After washing with anhydrous ethanol, a covalently bonded graphene film (US-CrGO) was obtained. The film was then soaked in a 10 mM BPATD DMF solution for 24 h, then washed with DMF 5 times to remove the BPATD on the film surface, and finally irradiated under 254 nm and 365 nm UV lamps for 2 h, respectively, to obtain a confined ordered cross-linked graphene composite film. By adjusting the height of the doctor blade, a US-SB-rGO film with a thickness ranging from 0.5 to 10 μm can be obtained. The obtained US-SB-rGO film has a tensile strength of 1.97 GPa and a modulus of 107.67 GPa.
[0048] Example 3
[0049] Take 30 mL of the GO dispersion (2 mg mL -1) was placed in a 50 mL centrifuge tube and centrifuged at 10000 rpm for 10 min to obtain GO gel. After fully removing the bubbles in the gel, the graphene oxide gel film was prepared by scraping on a hydrophilic polyvinylidene fluoride (PVDF) porous substrate. The gel film was transferred to a stretching device and continuously stretched and dried naturally to obtain a US-GO film. The film was kept in a stretched state and reduced with 38 wt% hydroiodic acid for 12 h. After washing with anhydrous ethanol, a graphene film (US-rGO) was obtained. The height of the scraping can be adjusted to obtain a US-rGO film with a thickness range of 0.5-5 μm. The obtained US-rGO film has a tensile strength of 708.08 MPa and a modulus of 24.3 GPa.
[0050] Example 4
[0051] Take 30 mL of the GO dispersion (2 mg mL -1 ) was placed in a 50 mL centrifuge tube and centrifuged at 10000 rpm for 10 min to obtain GO gel. After fully removing the bubbles in the gel, the graphene oxide gel film was prepared by scraping on a hydrophilic polyvinylidene fluoride (PVDF) porous substrate. The gel film was transferred to a stretching device and continuously stretched and dried naturally to obtain a US-GO film. The film was kept in a stretched state and soaked in a 15 mM PCO DCM solution for 2 h, then washed with DCM 3 times, then reduced with 38 wt% hydroiodic acid for 12 h, then washed with anhydrous ethanol, and finally illuminated under a 254 nm ultraviolet lamp for 2 h to obtain a covalently bonded graphene film (US-CrGO). The height of the scraping can be adjusted to obtain a US-CrGO film with a thickness range of 0.5-5 μm. The obtained US-CrGO film has a tensile strength of 1071.08 MPa and a modulus of 55.68 GPa.
[0052] Example 5
[0053] Take 30 mL of the GO dispersion (2 mg mL -1) was placed in a 50 mL centrifuge tube and centrifuged at 10000 rpm for 10 min to obtain GO gel. After fully removing the bubbles in the gel, the graphene oxide gel film was prepared by scraping on a hydrophilic polyvinylidene fluoride (PVDF) porous substrate. The gel film was transferred to a stretching device and stretched and dried naturally to obtain a US-GO film. The film was kept in a stretched state, reduced with 38 wt% hydroiodic acid for 12 h, and then washed with anhydrous ethanol. The film was immersed in a 10 mM BPATD DMF solution for 24 h, and then washed with DMF 5 times to remove the BPATD on the surface of the film. Finally, it was illuminated under a 365 nm ultraviolet lamp for 2 h to obtain an ordered cross-linked graphene composite film. The height of the scraping can be adjusted to obtain a US-πrGO film with a thickness range of 0.5-10 μm. The obtained US-πrGO film has a tensile strength of 1355.99 MPa and a modulus of 65.42 GPa.
[0054] Example 6
[0055] Take 30 mL of the GO dispersion (2 mg mL -1 ) was placed in a 50 mL centrifuge tube and centrifuged at 10000 rpm for 10 min to obtain GO gel. After fully removing the bubbles in the gel, the graphene oxide gel film was prepared by scraping on a hydrophilic polyvinylidene fluoride (PVDF) porous substrate. The graphene oxide film was naturally dried and soaked in a 15 mM PCO DCM solution for 2 h, then washed with DCM 3 times, then reduced with 38 wt% hydroiodic acid for 12 h, and then washed with anhydrous ethanol to obtain a covalently bonded graphene film (CrGO). The film was then soaked in a 10 mM BPATD DMF solution for 24 h, then washed with DMF 5 times to remove the BPATD on the film surface, and finally irradiated under 254 nm and 365 nm UV lamps for 2 h, respectively, to obtain an ordered cross-linked graphene composite film. By adjusting the height of the scraping, a SB-rGO film with a thickness range of 0.5-10 μm can be obtained. The obtained SB-rGO film has a tensile strength of 1134.18 MPa and a modulus of 8.7 GPa.
[0056] Example 7
[0057] Take 30 mL of the GO dispersion (2 mg mL -1) was placed in a 50 mL centrifuge tube and centrifuged at 10000 rpm for 10 min to obtain GO gel. After fully removing the bubbles in the gel, the graphene oxide gel film was prepared by scraping on a hydrophilic polyvinylidene fluoride (PVDF) porous substrate. The graphene oxide film was naturally dried and placed in a 15 mM PCO DCM solution for 1 h, 2 h and 3 h, then washed with DCM 3 times, then reduced with 38 wt% hydroiodic acid for 12 h, washed with anhydrous ethanol, and finally illuminated under a 254 nm ultraviolet lamp for 2 h to obtain a covalently bonded graphene film (CrGO). The height of the scraping can be adjusted to obtain a CrGO film with a thickness range of 0.5-10 μm. Thermogravimetric analysis showed that the PCO content was 0.67%, 2.29% and 2.80%, respectively. When the PCO content was 2.29%, the tensile strength of the CrGO film obtained was 564.03MPa and the modulus was 4.85 GPa.
[0058] Example 8
[0059] Take 30 mL of the GO dispersion (2 mg mL -1 ) was placed in a 50 mL centrifuge tube and centrifuged at 10000 rpm for 10 min to obtain GO gel. After fully removing the bubbles in the gel, the graphene oxide gel film was prepared by scraping on a hydrophilic polyvinylidene fluoride (PVDF) porous substrate, and the graphene oxide film was naturally dried. Then, it was reduced with 38 wt% hydroiodic acid for 12 h, and then washed with anhydrous ethanol. The film was immersed in a 10 mM BPATD DMF solution for 12 h, 24 h, 36 h and 48 h, respectively, and then washed with DMF 5 times to remove the BPATD on the surface of the film. Finally, it was irradiated under a 365 nm ultraviolet lamp for 2 h to obtain a π-π conjugated cross-linked graphene composite film. By adjusting the height of the scraping, a πrGO film with a thickness range of 0.5-10 μm can be obtained. Thermogravimetric analysis showed that the BPATD contents were 7.8%, 10.7%, 11.2% and 12.0%, respectively. When the BPATD content was 10.7%, the tensile strength of the obtained πrGO film was 953.04 MPa and the modulus was 4.15 GPa.
[0060] Example 9
[0061] Take 30 mL of the GO dispersion (2 mg mL -1) was placed in a 50 mL centrifuge tube and centrifuged at 10,000 rpm for 10 min to obtain GO gel. After fully removing the bubbles in the gel, the graphene oxide gel film was prepared by scraping on a hydrophilic polyvinylidene fluoride (PVDF) porous substrate, and the graphene oxide film was naturally dried. Then, it was reduced with 38 wt% hydroiodic acid for 12 h, and then washed with anhydrous ethanol to obtain a graphene composite film rGO. The rGO film with a thickness range of 0.5-10 μm can be obtained by adjusting the height of the scraping. The obtained rGO film has a tensile strength of 419.62 MPa and a modulus of 5.09 GPa.
[0062] Example 10
[0063] The Herman orientation factor of the US-SB-rGO film prepared by confined ordered assembly (Example 2) is significantly higher than that of the rGO film (Example 9) due to the suppression of capillary shrinkage. The orientation factor of the film material was characterized by wide-angle X-ray scattering (WAXS XenocsNanoinxider analyzer). The characterization results show that the Herman orientation factor of the confined ordered assembly graphene film of Example 2 is 0.970 ( Figure 3 D), the orientation factor of rGO film is only 0.718 ( Figure 3 (D) The rGO film of Example 9 ( Figure 3 The cross-sectional FIB-SEM images of the US-SB-rGO film in (B) and Example 2 show that ( Figure 3 In the figure (A), there are no obvious pores in the US-SB-rGO film, which has a more compact structure. Comparison of the porosity of the rGO film and the US-SB-rGO film ( Figure 3 In Figure C), the porosity of the rGO film is 15.7%, and the porosity of the US-SB-rGO film is 3.2%. This indicates that the capillary shrinkage of the film can be effectively suppressed by confined order, and the Herman orientation factor and density of the film can be improved.
[0064] Embodiment 11
[0065] The interlayer spacing of the US-SB-rGO film prepared by confined ordered assembly (Example 2) is significantly lower than that of the SB-rGO film prepared by scraping ordered assembly (Example 6) due to the suppression of capillary contraction. The scattering vector q of the film material was characterized by wide-angle X-ray scattering, indicating that the interlayer spacing of the confined ordered assembly graphene film US-SB-rGO in Example 2 is 3.67 Å, which is significantly lower than the interlayer spacing of the SB-rGO film prepared by scraping ordered assembly in Example 6 ( Figure 4 A in the middle). The interlayer spacing of the film material was also characterized by an X-ray scattering instrument. The characterization results showed that the interlayer spacing of the confined ordered assembled graphene film US-SB-rGO of Example 2 was 3.78 Å ( Figure 4 In B), the interlayer spacing of the SB-rGO film prepared by blade coating orderly assembly in Example 6 was reduced to 3.67 Å ( Figure 4 In B), the interlayer spacing of rGO film is 3.67 Å ( Figure 4 At the same time, the TEM images of the SB-rGO film of Example 6 and the US-SB-rGO film of Example 2 show that the US-SB-rGO film has a more regular orientation structure and a smaller lattice spacing ( Figure 4 (F) The rGO film and SB-rGO film have irregular structures due to capillary contraction, with the maximum lattice spacing of 3.78 Å ( Figure 4 E), the rGO film also has an irregular structure due to capillary contraction, which is more irregular than the confined and orderly assembled graphene composite film US-SB-rGO ( Figure 4 D). At the same time, differential scanning calorimetry ( Figure 4 C) Experiments show that the glass transition temperature of the US-SB-rGO film, which is orderly assembled by effectively suppressing the capillary shrinkage of the film through continuous external force stretching, is 171.84 °C, which is significantly higher than the glass transition temperature of 159.84 °C of the SB-rGO film prepared by orderly assembly by scraping in Example 6, but both are higher than the glass transition temperature of 114.58 °C of the polymer BPATD, indicating that BPATD in the confined domain assembled US-SB-rGO film is more likely to undergo 1,4 addition polymerization under ultraviolet light, thereby introducing new carbon-carbon double covalent bonds. At the same time, due to the continuous stretching that suppresses capillary shrinkage, the US-SB-rGO film has a smaller interlayer spacing, indicating that the polymer BPATD and the US-SB-rGO film produce a stronger π-π interaction.
[0066] Example 12
[0067] The confined ordered assembly graphene composite film (US-SB-rGO) material effectively inhibits capillary contraction and introduces interface synergy to improve film orientation and density, thereby preparing a graphene composite film with high mechanical properties. Compared with the rGO film of Example 9, the tensile strength (419.62 MPa) and Young's modulus (5.09 GPa) of the US-SB-rGO film increased to 1.97 GPa and the modulus was 107.67 GPa ( Figure 5 A). The decreasing frequency of the Raman G peak wavenumber in the in-situ tensile test characterizes the stress transfer efficiency between nanosheets ( Figure 5 C, F), the results show that compared with rGO film ( Figure 5 Middle F), US-SB-rGO composite membrane nanosheets ( Figure 5 C) shows a monotonically increasing stress transfer efficiency. When the strain is 2.0%, the G-band frequency decreases by 12.7 cm-1 , with high stress transfer efficiency. The stress relaxation test is used to characterize the film's ability to withstand dynamic loads ( Figure 5 D), the results show that the US-SB-rGO film can maintain 93.9% of the initial stress at 1% strain for 25,000 s, which is much higher than the rGO film (32.1%). SEM shows that the rGO fracture is flat ( Figure 5 E), but the US-SB-rGO film showed obvious curling, indicating that the US-SB-rGO film has stronger interfacial forces ( Figure 5 By comparing the mechanical properties with other graphene films reported in the literature ( Figure 5 G), it can be seen that the tensile strength and Young's modulus of the US-SB-rGO film prepared by the confined ordered assembly method are higher than those of the same type of films reported in the literature (Adv. Mater. 2020, 32, e1907411.;Nat. Commun. 2020, 11, 1.;Nat. Mater. 2021, 20, 624.).
[0068] It should be noted that, according to the above-mentioned embodiments of the present invention, those skilled in the art can fully implement the full scope of the independent claims and dependent rights of the present invention, and the implementation process and method are the same as the above-mentioned embodiments; and the parts not elaborated in detail in the present invention belong to the well-known technology in the field.
[0069] The above descriptions are only some specific implementation methods of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any person familiar with the art within the technical scope disclosed in the present invention should be covered within the protection scope of the present invention.
Claims
1. A method for preparing a π-π conjugated molecule confined polymerization graphene composite film material, characterized in that: The following steps are involved: Step 1, reacting raw graphite powder with 98 wt% concentrated sulfuric acid and potassium permanganate at low temperature, washing and centrifugal peeling to prepare a single-layer graphene oxide dispersion; Step 2: The graphene oxide dispersion obtained in step 1 is coated on a hydrophilic polyvinylidene fluoride porous substrate to form a graphene oxide gel film with a thickness of 100-1000 microns; Step 3, preparing the graphene oxide gel film obtained in step 2 into a graphene oxide film by a method of continuous external force stretching; Step 4, covalently cross-linking the graphene oxide film obtained in step 3 with a cross-linking agent containing long-chain hydroxyl molecules under continuous external tensile force to obtain a covalently cross-linked graphene oxide film; Step 5, reducing the covalently cross-linked graphene oxide film obtained in step 4 with a reducing agent under the action of external tensile force to obtain a covalently cross-linked graphene film; Step 6, washing the covalently cross-linked graphene film obtained in step 5 with a detergent under continuous external tensile force, immersing it in a cross-linking agent solution for cross-linking, and drying it to prepare an ordered cross-linked graphene carbon film material; Step 7: The ordered cross-linked graphene film obtained in step 6 is subjected to external tensile force, washed, and polymerized under 254 nm and 365 nm ultraviolet light, respectively, to prepare a π-π conjugated molecular confined polymerization graphene composite film material.
2. The method according to claim 1, characterized in that: In the step 1, the low temperature is 5°C to 10°C; and the diameter of the single-layer graphene oxide nanosheet is 5-60 μm.
3. The method according to claim 1, characterized in that: In the step 2, the speed of the scraping is 10 mm / s to 100 mm / s, and the temperature of the scraping is 25° C. to 35° C.
4. The method according to claim 1, characterized in that: In the step 3, the graphene oxide gel film is regularly oriented under continuous external stretching.
5. The method according to claim 1, characterized in that: In step 4, the cross-linking agent is a dichloromethane solution of 10,12-pentacadiyn-1-ol, the concentration of the 10,12-pentacadiyn-1-ol is 15 mM, the mass fraction of the 10,12-pentacadiyn-1-ol is 0.5-3%, and the cross-linking reaction time is 1-3 h.
6. The method according to claim 1, characterized in that: In step 5, the reducing agent is hydroiodic acid, and the reduction reaction time is 12 h.
7. The method according to claim 1, characterized in that: In the step 6, the detergent is anhydrous ethanol, the cross-linking agent is an N,N-dimethylformamide solution of π-π conjugated long-chain molecules with phenanthroline rings at both ends, the concentration of the π-π conjugated long-chain molecules with phenanthroline rings at both ends is 10 mM, the mass fraction of the π-π conjugated long-chain molecules with phenanthroline rings at both ends is 5-15%, and the immersion reaction time is 12-48 h.
8. The method according to claim 1, characterized in that: In step 7, the detergent used for washing is N,N-dimethylformamide, the light efficiency of ultraviolet light with a wavelength of 254 nm is 30 W, and the illumination time is 2 h, and the light efficiency of ultraviolet light with a wavelength of 365 nm is 500 W, and the illumination time is 2 h.
9. A π-π conjugated molecular confined polymerized graphene composite film material prepared by the method according to any one of claims 1 to 8, characterized in that: The Herman orientation factor of the graphene composite film material is 0.970, the porosity of the graphene composite film material is 3.20%, the thickness of the graphene composite film material is 0.5-10 μm, the tensile strength of the graphene composite film material is 1.97 GPa, and the modulus of the graphene composite film material is 107.67 GPa.
Citation Information
Patent Citations
Preparation method of conducting shell-like layered graphene composite material
CN102924274A
High-strength high-tenacity high-conductivity graphene membrane and preparation method thereof
CN108147393A
Preparation method of high-strength and high-conductivity graphene film
CN112174120A
Highly conducting and oriented graphene film and production process
US20170162291A1
